2021
DOI: 10.2196/preprints.34059
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of a Mobile and Wearable Device Intervention on Increased Physical Activity to Prevent Metabolic Syndrome: Observational Study (Preprint)

Abstract: BACKGROUND Research on whether wearable devices and app-based interventions can effectively prevent metabolic syndrome (MetS) by increasing physical activity (PA) among middle-aged people living in the rural areas of South Korea remains insufficient. OBJECTIVE The aim of this study was to determine whether mobile and wearable device interventions can improve health indicators, including PA, in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In addition, Schraplau et al (Schraplau et al, 2021) reported that a preventive effect could be achieved by combining a mobile diagnostic approach with an intervention program that includes lifestyle monitoring through wearables and mobile applications, especially nutrition and exercise programs that can be easily integrated into daily routines. These results are attributed to the importance of additional education on metabolic syndrome, normal baseline, correct eating habits, and increased activity (Kim et al, 2022).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition, Schraplau et al (Schraplau et al, 2021) reported that a preventive effect could be achieved by combining a mobile diagnostic approach with an intervention program that includes lifestyle monitoring through wearables and mobile applications, especially nutrition and exercise programs that can be easily integrated into daily routines. These results are attributed to the importance of additional education on metabolic syndrome, normal baseline, correct eating habits, and increased activity (Kim et al, 2022).…”
Section: Discussionmentioning
confidence: 98%
“…Wearable devices can promote health behavior change, but their successful use and potential health benefits depend more on the design of an engagement strategy than on the nature of the technology (Patel et al, 2012). Here, the need for individual encouragement, competition and collaboration, and effective feedback related to human behavior is emphasized (Kim et al, 2022). In this study, personalized knowledge and information provided through mobile notifications and apps acted as a major factor in preventing MetS by continuously maintaining the recommended PAs presented by guidelines in Korea and the United States.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation